What I Did On My Summer Vacation: I Accidentally Conducted a Personal Study of Integrative Care - Jeffrey Draisin MD (SAGE Publishing, 2019)
As a physician, I am a regular witness to transformative experience and its aftermath. The source of the experience doesn't seem to matter-a grave diagnosis, a trek up Mount Everest, a devastating loss. The need to question, to look at essential values, assumptions, and priorities is urgent and compelling. The answers galvanize intention, injecting it with potency. Patients realize they are living in a habitual way and their responses have some universality. They describe a new clarity and sense of self. They're emboldened. They are more connected to life and to people who love them. Often they have a new sense of meaning and purpose to being alive. In August, I had my own transformative experience. What I did not expect was that my experience would validate for me the integrative approach from the inside out. From my heart.